Modification of Montmorillonite K10 with Al3+ and its Potential in Biodiesel Production - Siti Mariam Muhamad Sabri; Syahirah Yahya; Farah Hanis Razali; Farah Wahida Harun (Universiti Sains Islam Malaysia, 2024)
Biodiesel is a green fuel diesel, which is used to fuel compression-ignition engines, same as petroleum diesel. By using waste cooking oil (WCO) as raw material, the production of biodiesel requires two-steps esterification-transesterification reactions involving acid catalyst and basic catalyst, respectively. Most researchers used strong acid (i.e. H2SO4) followed by a strong base (i.e. NaOH) to enhance the biodiesel products. However, apart from corrosion potential, these homogeneous catalysts also take extra time and cost for the purification process. To overcome this problem, a bi-functional catalyst is required so that the reactions can undergo simultaneously. In this research, WCO for the production of biodiesel was characterized. A bi-functional catalyst was produced by modification of montmorillonite K10 (MMT K10) clay with Al3+ ion creating Al-MMT K10 catalyst, followed by characterization of Al-MMT K10 using temperature-programmed desorption of ammonia (TPD-NH3) and scanning electron microscopy with energy dispersive x-ray spectroscopy (SEM/EDX). Lastly, the catalytic activity was examined by producing biodiesel known as fatty acid methyl ester (FAME) with conditions 10:1 to 14:1 (mol ratio of methanol : WCO), 2 to 4 wt. % of catalyst loading, 4 to 6 hours reaction time and 90 to 130 °C reaction temperature using GC-FID. After modification, the weight percentage of Al in MMT K10 was increased by 0.8 % and the acidity was increased by 1200.97 ?mol/g NH3. By optimizing the parameters using 6 % Al-MMT K10 at 110 °C with 12:1 (methanol:WCO) within 6 hours reaction, 42.47 % acid conversion and 40 % of FAME yield was achieved. It is expected that up to 80 % of biodiesel can be achieved by optimizing the Al composition in MMT K10 clay. In conclusion, Al-MMT K10 was successfully acted as bi-functional catalyst for esterification and transesterification of WCO in biodiesel production.